(untitled) (Research, Society and Development, 2022)
The context of breastfeeding experienced by mothers of premature newborns is the main issue of this article, considering the needs of growth, neurological development, clinical stability and thermoregulation control for the initiation of early stimulation of breastfeeding. On the other hand, we have the sociocultural condition of the mother who needs support and guidance from the multidisciplinary team to cross the situations that come from the hospitalization of her child in the neonatal unit. In this way, it is essential to provide health education on breastfeeding and daily care for premature infants. This article lists breastfeeding practices in neonatal units from 2015 to 2020. Integrative review of the literature conducted in the Virtual Health Library and MEDLINE, LILACS and BDENF databases using the descriptors in Health Sciences (DeCS): breastfeeding, premature newborn, neonatal ICU; in six phases: preparation of the review question, search of articles according to inclusion and exclusion criteria, data collection, critical analysis of selected articles, discussion of results and presentation of the review. Selected 148 articles, of these 20 articles composed the review. Level of evidence of the articles included: 05 meta-analyses - Level I, 07 cross-sectional studies - Level IV, 06 descriptive qualitative studies and 02 integrative reviews - Level V. The evidence described in the analyzed articles corroborates that breastfeeding combined with available health technologies increases the survival of premature infants. Policies and strategies for strengthening breastfeeding of premature infants should be implemented in public health policies.